Levitin-Polyak Well-Posedness of Constrained Inverse Quasivariational Inequality. (2nd January 2017) - Virmani, Garima; Srivastava, Manjari
ABSTRACT: In this article, we introduce and study different types of Levitin–Polyak well-posedness for a constrained inverse quasivariational inequality problem. Criteria and characterizations for these types of well-posedness for inverse quasivariational inequality problems are given. Suﬃcient conditions for the Levitin–Polyak well-posedness of inverse quasivariational inequality problems are also established.